2011
DOI: 10.1016/j.jclinepi.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review highlights difficulty interpreting diverse clinical outcomes in abnormal uterine bleeding trials

Abstract: Objectives (1) To systematically collect and organize into clinical categories all outcomes reported in trials for abnormal uterine bleeding (AUB); (2) to rank the importance of outcomes for patient decision making; and (3) to improve future comparisons of effects in trials of AUB interventions. Study Design and Setting Systematic review of English-language randomized controlled trials of AUB treatments in MEDLINE from 1950 to June 2008. All outcomes and definitions were extracted and organized into major ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 29 publications
0
53
0
1
Order By: Relevance
“…6,7 Quality of life is not measured in a standardized fashion across studies on AUB and little information is available on the impact of AUB on quality of life measures from a national population-level perspective. 6,7,8 The available population-level studies have shown that women with AUB have increased utilization of health resources compared to women without AUB.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Quality of life is not measured in a standardized fashion across studies on AUB and little information is available on the impact of AUB on quality of life measures from a national population-level perspective. 6,7,8 The available population-level studies have shown that women with AUB have increased utilization of health resources compared to women without AUB.…”
Section: Introductionmentioning
confidence: 99%
“…The task of comparing the different types of therapies is difficult because of the subjective and variable nature of the presenting symptoms in dysfunctional uterine bleeding [33]. The importance of each outcome measure was graded on a scale designed by the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) working group [34].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of each outcome for clinical decision making was determined by consensus in the SGS-SRG [8]. The systematic review for this guideline included only outcomes of critical or high importance.…”
Section: Methodsmentioning
confidence: 99%
“…In developing this guideline, we were faced with inconsistent measurement and reporting of a great number of outcomes [8]. We addressed this by categorizing outcomes and ranking their relative importance to weigh results when determining the net balance of benefits and harms.…”
Section: Limitations Of the Evidence Basementioning
confidence: 99%